A novel variant in the HX repeat motif of ATN1 in a Chinese patient with CHEDDA syndrome and literature review. Issue 12 (17th October 2022) - Luo, Sukun; Hu, Yanqiu; Xiong, Ping; Tan, Li; Zhao, Peiwei; Huang, Yufeng; Xiao, Cuiping; Zhu, Hongmin; He, Xuelian
Abstract: Background: CHEDDA syndrome is a rare neurodevelopmental syndrome caused by heterozygous missense or indel variants in the HX repeat motif of ATN1 gene. To date, CHEDDA has been identified in a few ethnic groups, and only 17 patients have been reported in literature, and no case has been reported in any country or region in Asia. Methods: Trio‐exome sequencing (Trio‐ES) examination was conducted in a Chinese girl with global developmental delay and in her parents. Sanger sequencing was performed to confirm the candidate variant. Results: This patient presented with mental and motor developmental delay, speech delay, and mild dysmorphic facial features, and had no epilepsy and visual impairment. Brain MRI did not show obvious structural abnormality. Through ES we identified a novel and de novo variant, c.3176_c.3177insGCACCT (p.Ser1059_His1060insHisLeu), within the HX motif of ATN1 . No other pathogenic variant in another gene was found to support an alternative clinical and molecular diagnosis. Conclusions: This is the first described case of CHEDDA from China. Together with the available literature data, we found that either disruption of HX motif or alteration of the HX repeat number would lead to ATN1‐associated CHEDDA. We also noted that CHEDDA is a clinical heterogenous syndrome, and patients carrying the same or similar variant might have different clinical manifestations and prognosis. Abstract : This is the first Chinese case with CHEDDA, and our patient carried an insertion of a histidine and leucine has milder motor developmental delay, which is consistent with previous observatons, although with high heterogeneity.